PERSPECTIVES OF BLOCKCHAIN TECHNOLOGY IN BUSINESS AND MANAGEMENT: ADVANTAGES AND CHALLENGES - Merinova, S. V.; Romanuke, V. V. (Systems and Technologies, 2025)
Blockchain is a decentralized and distributed digital ledger technology that records transactions across multiple computers. The key idea is that once information is recorded on a blockchain, it is extremely difficult to alter or tamper with because each block in the chain contains a cryptographic hash of the previous block, a timestamp, and transaction data. This creates a secure, transparent, and immutable system. In this paper, we review the key features of blockchain and examples of its particular application in business and management. In Ukraine, while blockchain technology has a huge potential to change many business sectors, providing security, transparency and efficiency of processes, it is necessary to solve the issues of scalability, regulatory barriers, as well as optimize energy consumption for full implementation. The future of blockchain in business and management looks promising, especially given the opportunities offered by smart contracts, decentralized finance, and asset tokenization. The today’s leading trend is energy trading whose blockchains have been increasingly used to record and publish local and regional electricity market data. This is believed to produce a significant impact on establishing and solidifying transparency of pricing and investing in energy sector. Solving current problems will allow blockchain technology to become the main tool for creating transparent and reliable business processes. However, scalability still remains the most serious and pressing problem in blockchain implementation. While significant advancements are being made to address it, the unsolved balance between scalability, security, and decentralization (the blockchain trilemma) presents ongoing technical, economic, and environmental challenges.